Answer:
Step-by-step explanation:
given that f(a) = K
we have the options of
f(K) = a
f ⁻¹ (K) = a
f ⁻¹ (a) = K
Where f ⁻¹ denotes an inverse function.
If f(a) = K, then its reciprocate, f ⁻¹ (K) = a
because it is essentially undoing the original equation
Answer:
C) I only
Step-by-step explanation:
( -1, -2) and (0,4)
Slope:
m=(y2-y1)/(x2-x1)
m=(4+2)/(0+1)
m=6/1
m=6
Slope-intercept:
y - y1 = m(x - x1)
y + 2 = 6(x + 1)
y + 2 = 6x + 6
y = 6x + 4
y - 16 = 6(x - 2)
y - 16 = 6x - 12
y = 6x + 4
I will solve your system by substitution.<span><span>x=<span>−2</span></span>;<span>y=<span><span><span>23</span>x</span>+3</span></span></span>Step: Solve<span>x=<span>−2</span></span>for x:Step: Substitute<span>−2</span>forxin<span><span>y=<span><span><span>23</span>x</span>+3</span></span>:</span><span>y=<span><span><span>23</span>x</span>+3</span></span><span>y=<span><span><span>23</span><span>(<span>−2</span>)</span></span>+3</span></span><span>y=<span>53</span></span>(Simplify both sides of the equation)
Answer:<span><span>x=<span>−<span><span>2<span> and </span></span>y</span></span></span>=<span>5/3
<span>
so the answer is B (the second choice)
(Hope it helped ^_^)
</span></span></span>
it is c. because the function is not a dependent or independent variable
Answer:
1) 117
2) 51
3) congruent
4) to each other
Step-by-step explanation: